Diversity of macroinvertebrate along Sungai Asah in Pulau Tioman, Johor, Malaysia - Suganthi Appalasamy; Nivaarani Arumugam; Sayzwani Sukri; Aweng Eh Rak (2016)
To gauge the quality of river in terms of biological health, an investigation on the distribution of macroinvertebrate along Sungai Asah, Pulau Tioman, Pahang at three main stations i.e. downstream, mainstream and upstream was done in April 2016. The macroinvertebrates in Sungai Asah was represented by nine orders, 45 families and 329 individuals from all three sampling stations. The family was commonly found at this river is Diptera contributing 99 individuals of the total macroinvertebrates followed by Trichoptera (80 individuals) and the least found in Sungai Asah is Haplotaxida taxa with only two individuals from the midstream station. Among the sampling sites, the midstream sampling station has the highest abundance of macroinvertebrate individuals (47.11%) followed by the upstream stations and the downstream station. Pollutioin intolerant taxa Ephemeroptera was found at all sampling stations. However the macroinvertebrates from this order was abundant only at upstream and midstream. In terms of indices, although the biological monitoring working party (BMWP) score at the midstream of the river indicated the area was not impacted with pollution but the EPT index fall in the Poor (2.8) category which could be due to the usage of the area for recreational and human activity such as swimming and bathing. There are also very low number of aquatic macroinvertebrates from Odonata recorded in Sungai Asah which could also indicate that Sungai Asah is disturbed and impacted by the human recreational activity hence it is unhealthy.